المعوقات القانونية لتنمية الوقف في المملكة العربية السعودية : دراسة تأصيلية تحليلية - عقلا، عقيل محمد علي (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2021)
The present research aims at idetifying the The legal obstacles of waqf's development in the kingdom of Saudi Arabia : an original and analytical study. In addition، it aims at finding the reasons behind these obstacles .The study analyses the results، provides suggestions and recommendations to overcome these obstacles. The research، also، discusses the arguments of the critics who called for eliminating the charitable endowments in the same way of abolishment of civil charitable investments in some Islamic countries. It provides answers for these arguments and calls for detailed monitoring for the movement of reducing the legislations rules related to endowments in the country of the Two Holy Mosques. The researcher uses several approaches including the deductive and descriptive approaches as well as the inductive approach through the personal viewpoint of the researcher to identify the legal obstacles، their causes and resulting outcomes. This is done to find solutions to develop the Islamic endowments and reform the legal construction for endowment through the deductive and inductive literature review of endowment. The salient findings of this research assure the importance of adapting the regulations of controlling accountability، and legal auditing systems that are implemented in business or commercial institutions. This procedure aims at fostering the preservation of the fundamental assets of endowments and its resources، plus ensuring the enhancement of endowments' assets and investing their excess financial resources in various investment fields where the return is highly expected and the risks are low . This could help to increase the shares of the beneficiaries concerned and raise their real incomes. Furthermore، procedure aims at facing the problem the increasing numbers of the partners and the deteriorating purchasing power of their cash incomes. The study has also highlighted ، the importance of strategical planning for endowment's funding development and investment to reach the average of real private investment